2010
DOI: 10.1192/bjp.bp.109.075135
|View full text |Cite
|
Sign up to set email alerts
|

Process, outcome and experience of transition from child to adult mental healthcare: multiperspective study

Abstract: For the vast majority of service users, transition from CAMHS to AMHS is poorly planned, poorly executed and poorly experienced. The transition process accentuates pre-existing barriers between CAMHS and AMHS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
466
3
23

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 322 publications
(528 citation statements)
references
References 14 publications
36
466
3
23
Order By: Relevance
“…This may not regularly occur because young adults with chronic medical and mental health conditions are particularly vulnerable to disrupted medical care during the years of transition from pediatric to adult care (39,40). This study suggests that mental health and eating disturbances in particular should be an important clinical focus of effective transition and continuity of care for young women with type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…This may not regularly occur because young adults with chronic medical and mental health conditions are particularly vulnerable to disrupted medical care during the years of transition from pediatric to adult care (39,40). This study suggests that mental health and eating disturbances in particular should be an important clinical focus of effective transition and continuity of care for young women with type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Singh and colleagues found that for the vast majority of service users, transition from children's mental health to adult mental health services was poorly planned, poorly executed, and poorly experienced. 22 The physical health needs of people with psychosis are well documented, 23,24 and reflected in English national guidance. 25,26 However, this paper suggests that both primary and secondary care health services and service users themselves have yet to respond fully to the physical health challenges posed by the condition, lifestyle, and treatments.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…As an iterative process, it enabled amendment and additions to the analytic framework throughout, grounding the analysis in participants' accounts. The Framework method allowed for dyadic analysis (Akeson et al, 2007;Ellis et al, 2012;Singh et al, 2010), aided by separate interviews for patients and their partners (Eisikovits & Koren, 2010).…”
Section: Designmentioning
confidence: 99%